Processability theory and pedagogical progression in an Italian textbook - Zipser, Katharina (Linguistica (Ljubljana), 2012)
Most L2-learners are taught a language on the basis of a textbook. But are these textbooks arranged according to the learners' needs? For the present study the grammatical structures and their progression in an Italian-language textbook were analysed, and they were compared to the learners' speaking ability to cross-check the degree of correspondence between what is taught following the textbook and what is actually learned. The question is asked in how far textbook design should consider the findings of current SLA research. It is suggested that even though Processability Theory is right to predict that language acquisition develops in stages, instruction need not be strictly sequenced. Above all it is important to distinguish between input, intake and expected output.
Keywords: acquisition du langage; acquisition graduelle; capacité linguistique; grammaire; grammar; Italian; italien; italijanščina; jezikovna zmožnost; manuels; slovnica; stopenjskost; učbeniki; usvajanje jezika